Membrane Depolarization and Apoptosis-Like Cell Death in an Alkaline Environment in the Rice Pathogen Burkholderia glumae - Nam, Yewon; Goo, Eunhye; Kang, Yongsung; Hwang, Ingyu (Frontiers in Microbiology, 2021)
The rice pathogen Burkholderia glumae uses amino acids as a principal carbon source and thus produces ammonia in amino acid-rich culture medium such as Luria-Bertani (LB) broth. To counteract ammonia-mediated environmental alkaline toxicity, the bacterium produces a public good, oxalate, in a quorum sensing (QS)-dependent manner. QS mutants of B. glumae experience alkaline toxicity and may undergo cell death at the stationary phase when grown in LB medium. Here, we show that the cell-death processes of QS mutants due to alkaline environmental conditions are similar to the apoptosis-like cell death reported in other bacteria. Staining QS mutants with bis-(1,3-dibutylbarbituric acid)-trimethine oxonol revealed membrane depolarization. CellROX™ staining showed excessive generation of reactive oxygen species in QS mutants. The expression of genes encoding HNH endonuclease (BGLU_1G15690), oligoribonuclease (BGLU_1G09120), ribonuclease E (BGLU_1G09400), and Hu-beta (BGLU_1G13530) was significantly elevated in QS mutants compared to that in wild-type BGR1, consistent with the degradation of cellular materials as observed under transmission electron microscopy. A homeostatic neutral pH was not attainable by QS mutants grown in LB broth or by wild-type BGR1 grown in an artificially amended alkaline environment. At an artificially adjusted alkaline pH, wild-type BGR1 underwent apoptosis-like cell death similar to that observed in QS mutants. These results show that environmental alkaline stress interferes with homeostatic neutral cellular pH, induces membrane depolarization, and causes apoptosis-like cell death in B. glumae.